(untitled) (Journal of Hama University, 2019)
The Olive Solid Waste (OSW) was fermented according Fermentation System Aerobic for four times (0,1,2,3,4 month) pH, EC, organic carbon, total nitrogen, organic matter, ash, (C/N rato), phosphorus, potassium, calcium and magnesium were determined. The aim of this paper was to determine the optimal time for the fermentation of the OSW and its effect on some of its chemical properties and fertility. The study led to the following results: The decrease of pH in the fermented OSW in the first and second months reached 6.24 and 6.11 compared to zero time 6.5 and the pH values were increased in the third month and reached in the fourth month to 6.98 and the salinity concentration increased after four months when the EC reached 1.59 dS/m. Significant decrease in the percentage of organic carbon with an increase in fermentation time,it was in the fourth month 37.36% compared to zero time 48.44%. Both fermented OSW after 3 months and 4 months showed significant differences in N content and organic matter compared to zero time, 1 and 2 months. Where the highest percentage N in the fermented OSW after four months 1.61% and the differences were not significant between three months and four months. The fermented OSW after three and four months showed that there were decreased in C/N ratio compared with others where the C/N ratio (68.22, 45.65, 33.21, 25.42 and 23.15) in zero time, one month, two months, three months and four months respectively. The percentage of phosphorus, potassium, calcium and magnesium increased in the third and fourth time compared to zero, first and second time. These percentages of P,K, Ca and Mg reached in the fourth time (0.82, 1.04, 0.75 and 0.55) % compared to zero time (0.33, 0.35, 0.30 and 0.21) % In the same previous order. The differences were not significant between the three months and four months